DIRECTIONS OF REGULATION OF THE ECONOMY BY THE STATE WITH THE HELP OF MONETARY POLICY (British Journal of Global Ecology and Sustainable Development, 2023)
This article describes in detail about the stable directions of regulation of the economy by the state with the help of monetary policy.